The goods of design professional ethics for designers - Guersenzvaig, Ariel, 1970- (Rowman & Littlefield, 2021)
"What is the true purpose of the design profession? What ends should professional designers pursue? Firmly rooted in the design practice, this lively and accessible book offers a critical vision that enables designers and students of design of all disciplines to reflect on the purpose of their profession. This book makes the case that professional designers should contribute to the promotion of others' well-being by designing a world in which people can flourish. Using many examples, it helps practitioners and students to analyse the ethics of the work they are asked to do, and guides them in designing material and immaterial artefacts that are conducive to human flourishing. The book also empowers them to discover and analyse the possible moral consequences of their designs, and to act thereupon. If design is, as Herbert Simon argued, 'concerned with how things ought to be', the influence designers have over the lives of others should not to be taken lightly"--